EVALUATION OF THE RESULTS OF COMPREHENSIVE REHABILITATION OF WOMEN OF FERTILE AGE WITH ACQUIRED EYELID DEFECT - Kamalova Mekhriniso Кilichevna; Kodirova Maftunabonu Komilovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the methods of surgical restoration of the original shape of the eyelids and periorbital areas with their deformities in women of childbearing age. The problem of treating patients is associated with the need to preserve or simultaneously restore the shape and functions of the eyelids, normal anatomical tissue relationships and aesthetically acceptable facial contours. The increased demand for aesthetic surgeries contributed to the active development of plastic surgery in Uzbekistan. In the literature sources studied by us, little attention is paid to the methods of surgical elimination of deformities of the eyelids and periorbital areas. All of the above served as the basis for conducting research and developing a system for the complex rehabilitation of patients with acquired eyelid deformities and defects.